Metabolic flux modeling of Gluconobacter oxydans enables improved production of bioleaching organic acids. (November 2022) - Aston, John E.; Thompson, Vicki S.; Fujita, Yoshiko; Reed, David W.
Abstract: Bioleaching with organic acids is an option for recovery of rare earth elements (REE) and or other valuable metals from consumer or industrial wastes. Biohydrometallurgy can play an economically and environmentally sustainable role in REE recycling, particularly if agriculture or food wastes are used as the carbon substrates for production of the bioleaching agents. A challenge for organic acid based REE bioleaching is the incomplete conversion of the carbon substrate to an optimal organic acid mixture with high REE extraction capability. To help meet this challenge a metabolic flux model was developed for Gluconobacter oxydans to identify options for improving sugar conversion to chelating organic acids. Model predictions were consistent with laboratory data for the microbial consumption of glucose and production of gluconic acid and suggested that providing growth conditions with relatively high carbon to nitrogen molar ratios could result in production of lower pH biolixiviant and thus improve REE bioleaching yields. Graphical Abstract: ga1 Highlights: A biochemical pathway model was developed to improve bioleaching with Gluconobacter. The model identified links between substrate addition and organic acid production. A high C:N molar ratio (>8) in the substrate resulted in improved biolixiviant.